UMP forges collaboration with Lumileds Sdn. Bhd. - Mohd Raizalhilmy, Mohd Rais (2020)
Penang, 27 July 2020 - Universiti Malaysia Pahang (UMP) strengthened its collaboration networking by inking a Memorandum of Understanding (MoU) with its strategic partner, Lumileds Sdn. Bhd.